Knowledge of pregnant women towards multiple sclerosis - Abbasi, Vahid; Tabrizian, Shervin; Atalu, Abolfazl; Aslanian, Roghayeh; Zakeri, Anahita (International Journal Of Community Medicine And Public Health, 2018)
Background: The multiple sclerosis (MS) disease is more common in women than men with a ratio of 2.7 to 1. According to Iran MS society, there are about 80,000 MS patients in the country Iran. Having knowledge about MS can reduce significantly the anxiety and stress of pregnant women and promote their life expectancy and the probability of having a successful pregnancy and making pregnancy easier for them. Methods: This is a descriptive– analytical study that has been done on 150 pregnant women which selected randomly and referred to health centers of Ardabil city at 2017. Data collected by a questionnaire included questions about MS. The collected data were analyzed by statistical methods in SPSS version 19. Results: Of all women, 20% considered gender as one of the most effective factors in the disease and 44.7% believed that women are more likely to suffer from MS than men. The knowledge of pregnant women about MS with 63.3% was in moderate level and friends and relatives was the most source of their awareness. 43.3% of women believed that knowledge people with MS could marry. 63.3% of women pointed that the health care centers knowledge about MS was inadequate and 68.7% pointed that government's support for patients was significantly low. Conclusions: Results showed that the awareness of pregnant women about MS was in moderate level. So, planning to increase the awareness of pregnant women in centers and support of women with MS by governmental centers seems necessary.